Physiological implications of preparing for a natural male bodybuilding competition. Issue 5 (28th May 2018) - Mitchell, Lachlan; Slater, Gary; Hackett, Daniel; Johnson, Nathan; O'connor, Helen
Abstract: This study aimed to describe the body composition and physiological changes which take place during the in-season and recovery periods of a group of natural bodybuilders. Natural male bodybuilders ( n = 9) were assessed 16 (PRE16), 8 (PRE8), and 1 (PRE1) week(s) before, and 4 (POST4) weeks after a bodybuilding competition. Assessments included body composition, resting metabolic rate (RMR), serum hormones, and 7-day weighed food and training diaries. Change in parameters was assessed using repeated-measures analysis of variance. Dietary protein intake remained high throughout the study period (2.8–3.1 g kg −1 d −1 ). Fat mass (FM) was significantly reduced from PRE16 to PRE1 (8.8 ± 3.1 vs. 5.3 ± 2.4 kg, P < .01). There was a small decrease in lean mass (LM) from PRE8 to PRE1 (71.8 ± 9.1 vs. 70.9 ± 9.1 kg, P < .05). No changes in RMR were observed ( P > .05). Large reductions in total and free testosterone (16.4 ± 4.4 vs . 10.1 ± 3.6 nmol L −1, P < .05; 229.3 ± 72.4 vs . 116.8 ± 76.9 pmol L −1, P < .05), and insulin-like growth factor-1 (IGF-1) (27.0 ± 7.7 vs . 19.9 ± 7.6 nmol L −1, P < .05) occurred between PRE16 and PRE1. LM and IGF-1 increased from PRE1 to POST4 (70.9 ± 9.1 vs . 72.5 ± 8.5 kg, P < .05; 19.9 ± 7.6 vs . 25.4 ± 9.3 nmol L −1, P < .05). Despite substantial reductions in FM, participants maintained almost all of their LM. The reduction in anabolic hormone concentration is likely attributable to the prolonged negative energy balance, despite a high dietary protein intake.